HOW DISCLOSING SUSTAINABILITY PRACTICES AFFECTS FINANCIAL PERFORMANCE - Beatrice Tannessia Tandri; Widyasari Widyasari (Graduate Program of Universitas Tarumanagara, 2026)
This study empirically examines how sustainability reports, as measured by environmental, social, and governance (ESG) disclosures, affect the financial performance of firms in Indonesia. The analysis, which involved classical assumption tests followed by multiple regression, used Return on Equity (ROE) as the dependent variable for financial performance. The independent variables were categorized as environmental disclosures (ED), social disclosures (SD), and governmental disclosures (GD). Additionally, leverage (LEV) and firm size (SIZE) were included as control variables. A total of 124 observations were collected from 31 Indonesian companies spanning the period 2020 to 2023. This data, gathered using a purposive sampling method, included ESG data sourced from the Thomson Reuters index and financial figures (stated in Rupiah) from the companies’ annual reports. The collected data were subsequently subjected to outlier treatment using the EViews statistical software. Findings indicate that environmental disclosures, governmental disclosures, and leverage do not significantly impact financial performance. Conversely, social disclosures and firm size were found to be significant. Specifically, social disclosures showed a negative influence, while firm size had a positive influence on financial performance. This research is intended to provide valuable insights for various stakeholders, including investors, companies, and academic institutions, highlighting the differentiated impact of sustainability activities aspect particularly the social component on corporate financial performance within the Indonesian market.